Pronounced seasonality and eutrophication-driven dominance of Gephyrocapsa oceanica in Bohai Bay: A baseline assessment of living coccolithophores under anthropogenic pressure - Jiayao Shen; Haijiao Liu; Changling Ding; Jun Sun (Marine Environmental Research, 2026)

Phytoplankton community responses to natural and anthropogenic nutrient inputs in the Western Pacific Ocean: Insight from chemical taxonomy analysis - Zishi Liu; Wenzhuo Yan; Yujian Wen; Changling Ding; Jun Sun (Marine Pollution Bulletin, 2026)

Phytoplankton and carbon biomass dynamics in the South China Sea: responses to shelf-oceanic gradients and tropical cyclone - Changling Ding; Xingzhou Wang; Yi Long; Zishi Liu; Jun Sun (Marine Life Science & Technology, 2026)

Encapsulation of quercetin in zein/sodium caseinate nanoparticles: Fabrication, characterization, stability and controlled release properties - Peng Wang; Jinxia Wang; Huimin Hu; Nike Ding; Fenghua Wu; Guanyu Fang; Jing Mao; Changling Wu; Xingquan Liu (Food Research International, 2026)

Vertical zonation and interaction patterns of heterotrophic protists in the Bay of Bengal and Eastern Indian Ocean - Laxman Pujari; Qi Qiao; Sujata Nilajkar; Ting Gu; Danyang Li; Yiyan Guo; Xuelei Zhang; Lin Liu; Changling Ding; Jun Sun (Marine Pollution Bulletin, 2026)

The potential contribution of microbial communities to carbon fixation and nitrogen cycle in the Eastern Indian Ocean - Changling Ding; Jun Sun (Marine Environmental Research, 2025)

Investigation on performance enhancement and emission reduction of micro methanol steam reforming hydrogen reactor for proton exchange membrane fuel cell - Bo Luo; Jiaqiang E; Changling Feng; Xinyu Song; Jiangjun Ding; Wenming Yang (Journal of Cleaner Production, 2025)

Combined influence of the nanoplastics and polycyclic aromatic hydrocarbons exposure on microbial community in seawater environment - Xin Guan; Dai Jia; Xinyu Liu; Changling Ding; Jinfei Guo; Min Yao; Zhan Zhang; Mengxi Zhou; Jun Sun (Science of The Total Environment, 2024)

Spatial distribution and environmental/biological co-regulation mechanism of dimethyl sulfur compounds in the eastern Indian Ocean - Liying Peng; Chenjuan Fan; Yu Guo; Changling Ding; Xingzhou Wang; Guicheng Zhang; Jun Sun (Frontiers in Marine Science, 2024)
Dimethyl sulfur compounds including dimethylsulfoniopropionate (DMSP), dimethyl sulfide (DMS), and dimethyl sulfoxide (DMSO), play a crucial part in global sulfur cycling. The eastern Indian Ocean (EIO), characterized by its remarkable diversity of biomes and climate dynamics, is integral to global climate regulation. However, the regulation mechanism of DMS (P, O) in the EIO remains to be elucidated in detail. This paper presented a field survey aimed at investigating the spatial distribution of DMS (P, O) and their relationships with environmental and biological factors in the EIO. The surface concentrations of DMS, DMSPt, and DMSOt varied from 0.07 to 7.37 nmol/L, 0.14 to 9.17 nmol/L, and 0.15 to 3.32 nmol/L, respectively, and their distributions are attributed to high Chl-a concentration near Sri Lanka and the influence of ocean currents (Wyrtki jets, Bay of Bengal runoff). Higher concentrations of DMS (P) and DMSOt were predominantly observed in water columns shallower than 75m and deeper than 75m deep, respectively. The monthly DMS fluxes in the study area peaked in August. Temperature and Dissolved Silica Index (DSI) were the key environmental determinants for DMS distribution, while nitrate (NO 3 - ) was the primary factor for both DMSPt and DMSOt. In terms of biological factors, Prochlorococcus and Synechococcus were significant contributors to DMS (P, O) dynamics. Synechococcus was the dominant influence on the DMS source and DMSPt sink, whereas Prochlorococcus primarily consumed DMSOt. Furthermore, the structural equation modeling (SEM) revealed the relationship between DMS, DMSPt, DMSOt, and the key environmental/biological factors, as well as among them, and together they formed a co-regulatory network in the EIO. This contributes significantly to the advancement of global ecosystem models for DMS (P, O).

Effect of increased pCO2 and temperature on the phytoplankton community in the coastal of Yellow Sea - Xiaoting Fu; Jiahui Qin; Changling Ding; Yuqiu Wei; Jun Sun (Science of The Total Environment, 2024)

Dissolved and particulate heavy metal pollution status in seawater and sedimentary heavy metals of the Bohai Bay - Haijiao Liu; Changling Ding; Guicheng Zhang; Yiyan Guo; Yuyao Song; Satheeswaran Thangaraj; Xiaodong Zhang; Jun Sun (Marine Environmental Research, 2023)

Hypoxia in the Bohai Bay, China: distributions, causes and mechanisms - Guodong Zhang; Yujian Wen; Changling Ding; Guicheng Zhang; Jun Sun (Frontiers in Marine Science, 2023)
The Haihe River system is a major conduit of land-based pollution into the Bohai Sea in North China, This study presented the first-ever observation of hypoxia in the Haihe River estuary, providing valuable insights into the complex interplay between physical and biochemical factors influencing hypoxia in estuarine systems. The research found seasonal variations in DO distribution in the estuaries of the Haihe and Yongdingxin Rivers. Hypoxia emerged in summer at the bottom of the Haihe River estuary and dissipated in autumn, with the minimum DO concentration of 1.85 mg/L recorded at the bottom of the HH-2 station. Within the hypoxic zone, the average DO concentration was 4.02 mg/L, and the average of DO saturation was less than 0.4. This study also identified the primary drivers of summer hypoxia as a combination of physical and biochemical factors, with water stratification due to hydrodynamic factors limiting exchange and reoxygenation between different water layers. In addition, the decomposition of organic matter in the bottom consumed a significant amount of dissolved oxygen.The significantly higher DO concentration and saturation in autumn compared to summer suggested the possible existence of seasonal hypoxia in the Haihe estuary. This study of hypoxia in the Haihe River estuary contribute to a better understanding of the factors that influence seasonal hypoxia. The findings have important implications for the management and remediation of hypoxia in the Haihe estuary and other estuarine systems.

Transitional traits determine the acclimation characteristics of the coccolithophore Chrysotila dentata to ocean warming and acidification - Satheeswaran Thangaraj; Haijiao Liu; Yiyan Guo; Changling Ding; Il‐Nam Kim; Jun Sun (Environmental Microbiology, 2023)
Ocean warming and acidification interactively affect the coccolithophore physiology and drives major biogeochemical changes. While numerous studies investigated coccolithophore under short‐term conditions, knowledge on how different transitional periods over long‐exposure could influence the element, macromolecular and metabolic changes for its acclimation are largely unknown. We cultured the coccolithophore Chrysotila dentata , (culture generations of 1st, 10th, and 20th) under present (low‐temperature low‐carbon‐dioxide [LTLC]) and projected (high‐temperature high‐carbon‐dioxide [HTHC]) ocean conditions. We examined elemental and macromolecular component changes and sequenced a transcriptome. We found that with long‐exposure, most physiological responses in HTHC cells decreased when compared with those in LTLC, however, HTHC cell physiology showed constant elevation between each generation. Specifically, compared to 1st generation, the 20th generation HTHC cells showed increases in quota carbon (Qc:29%), nitrogen (Q N :101%), and subsequent changes in C:N‐ratio (68%). We observed higher lipid accumulation than carbohydrates within HTHC cells under long‐exposure, suggesting that lipids were used as an alternative energy source for cellular acclimation. Protein biosynthesis pathways increased their efficiency during long‐term HTHC condition, indicating that cells produced more proteins than required to initiate acclimation. Our findings suggest that the coccolithophore resilience increased between the 1st–10th generation to initiate the acclimation process under ocean warming and acidifying conditions.

The impact of environmental factors on the phytoplankton communities in the Western Pacific Ocean: HPLC-CHEMTAX approach - Guicheng Zhang; Zishi Liu; Zhaoyi Zhang; Changling Ding; Jun Sun (Frontiers in Marine Science, 2023)
The distribution characteristics, biomass, and communities of phytoplankton in the western Pacific Ocean (WPO) were investigated using high-performance liquid chromatography (HPLC)-CHEMTAX analysis. The results revealed significant differences in the distribution of phytoplankton communities among different water masses in the WPO. Haptophytes were the dominant group, followed by Prochlorophytes, Cyanobacteria, Prasinophytes, and Diatoms. The distribution of phytoplankton communities was primarily determined by the level of nitrate, phosphate, and silicate, while temperature showed a negative correlation with major phytoplankton communities. In the 130°E section, the divergence caused by Halmahera Eddy (HE) and Mindanao Eddy (ME) provided the abundant nutrients, making them the primary environmental influence factor near the equator. This divergence brought relatively eutrophic deep seawater into the euphotic layer, resulting higher biomass of phytoplankton communities. In the 20°N section, the distribution of phytoplankton was mainly influenced by the invasion of Kuroshio Current and its offshore flow. Additionally, due to the low surface-to-volume ratios, microphytoplankton dominated the phytoplankton community in this section instead of nanophytoplankton or picophytoplankton. In summary, this study confirms previous findings on distribution characteristics of phytoplankton and provides new insights into the environmental and biological regulations of phytoplankton communities in the WPO.

Nitrogen fixation driven by mesoscale eddies and the Kuroshio Current in the northern South China Sea and the East China Sea - Liuyang Li; Chao Wu; Jun Sun; Shuqun Song; Changling Ding; Danyue Huang; Laxman Pujari (Acta Oceanologica Sinica, 2020)

Morphology, ultrastructure and phylogeny of Cyanothece sp. (Cyanobacteriaceae: Cyanophyceae) isolated from the eastern Indian Ocean - Xiaodong Zhang; Shuang Yang; Jun Sun; Chao Wu; Jing Wang; Guicheng Zhang; Changling Ding (Acta Oceanologica Sinica, 2018)